2019
DOI: 10.5933/jkapd.2019.46.2.139
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Midpalatal Suture Maturation using Cone-Beam Computed Tomography in Children and Adolescents

Abstract: This study aimed to analyze the association of midpalatal suture (MPS) maturation stages with skeletal maturation and age and to obtain references for establishing a treatment plan for rapid maxillary expansion (RME). Cone-Beam Computed Tomography (CBCT) images from 480 children (240 boys, 240 girls) aged 7-15 years were obtained. MPS maturation stages and cervical vertebral maturation indicator (CVMI) were evaluated, and the correlations between MPS maturation stages, CVMI, and age were determined using the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Spearman correlation analysis showed a highly significant and positive correlation between MPS stage and CVM stage advocating that improvement (increase or decrease) in one may be directly associated with improvement (increase or decrease) in other. These findings were consistent with the findings of study done by Angelieri et al, 5 Jang et al, 20 and Lee et al 21…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Spearman correlation analysis showed a highly significant and positive correlation between MPS stage and CVM stage advocating that improvement (increase or decrease) in one may be directly associated with improvement (increase or decrease) in other. These findings were consistent with the findings of study done by Angelieri et al, 5 Jang et al, 20 and Lee et al 21…”
Section: Discussionsupporting
confidence: 93%
“…These findings were supported by the findings of the studies performed by Valdiva et al 14 and Tonello et al 19 Spearman correlation analysis showed a highly significant and positive correlation between MPS stage and CVM stage advocating that improvement (increase or decrease) in one may be directly associated with improvement (increase or decrease) in other. These findings were consistent with the findings of study done by Angelieri et al, 5 Jang et al, 20 and Lee et al 21 Highest sensitivity was found in pre-pubertal stages such as cervical vertebral maturation stage 1 and 2 for diagnosing MPS A and B, respectively. Skeletal maturity stages such as CVM stages 1, 2, and 3 had the likelihood ratio of more than 10, for MPS stage A, MPS stage B, and MPS stage C, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Formerly, chronological age had traditionally guided the clinical decision between traditional RME and SARME, but it has been proven in literature that this is an unreliable indicator for determining the maturation status of MPS [ 1 , 6 , 12 , 48 ]. This assertion can be supported by the present study, leading to a paradigm shift in the treatment of maxillary constriction.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal expansion is the widening of the maxilla by opening the midpalatal suture, whereas dentoalveolar expansion involves dental tipping and bending of the alveolar process. RME is aimed at maximizing the skeletal effect and reducing dentoalveolar effect, which may be accompanied by side effects, such as loss of the periodontal attachment level, fenestration of the buccal cortical bone, root resorption and palatal tissue necrosis [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have been conducted on relationships between the midpalatal suture maturation and skeletal development and reported that the maturation of the midpalatal suture is closely related to skeletal development [5][6][7][8]. These studies also have determined considerable variability in the chronologic age for ossification of the midpalatal suture [5,9].…”
Section: ⅰ Introductionmentioning
confidence: 99%